Chisinau Municipality as a Development Region of The Republic of Moldova - Victor PAVALEAN (CSIE Working Papers Series, 2020)
Regional development is the most rational way to a sustainable decentralization, meant to ensure the efficient response to guaranteeing democratic norms and principles, social equity, and sustainable economic development, based on special legal norms reflected in two fundamental legislative acts in this regard - Law no. 438-XVI of December 28, 2006, on regional development in the Republic of Moldova and Government Decision no. 158 of 04.03.2010 on the approval of the National Strategy for Regional Development, multiple legislative acts of a general nature, as well as various concepts promoted by academia and civil society.